Perancangan Konten Visual Instagram Ca-Fiber Untuk Meningkatkan Pemasaran - Rafif Virian Darmanto; Pungky Febi Arifianto (Pusat Riset dan Inovasi Nasional, 2023)
In this digital era, Instagram is one of the social media that is popular among people. This presents an opportunity for business people to carry out digital promotions. To promote a business, strong branding is needed.CA-Fiber is a company that operates in the creative industry sector in improving customer branding. As a company that focuses on branding, it must have a strong brand identity to attract customer attention. Good visual content design can help a business to show their branding. This design uses the design thinking method with the stages of empathize, define, ideate, prototype, and test.